A simple and convenient method to fabricate new types of phytic acid–metal conversion coatings with excellent anti-corrosion performance on the iron substrate. Issue 65 (22nd August 2017) - Yan, Ru; Gao, Xiang; He, Wei; Guo, Rui; Wu, Ruonan; Zhao, Zhuangzhi; Ma, Houyi
Abstract : A simple and practical method was developed to prepare phytic acid–metal complex coatings with excellent anti-corrosion performance on the iron substrate by making full use of the bridging effect of metal ions in the film-forming solution. Abstract : A simple and practical method was developed to prepare a series of phytic acid (PA)–metal complex coatings on iron substrate by directly immersing the iron samples in the mixed solutions containing PA and metal ions. The key technologies of fabricating PA–metal complex coatings include: (i) anchoring of PA molecules onto the iron surface via complexation with Fe 2+ ions dissolved from the iron substrate, and (ii) layer-by-layer deposition of PA–metal complexes on the PA/Fe 2+ bottom layer through the bridging effect of additive metal ions. The present method was applicable to the film-forming process of a variety of metal ions, such as Zn 2+, Ca 2+, Co 2+ and Ni 2+, and the as-prepared PA–metal complex coatings were defined as PA–M conversion coatings (M = Zn 2+, Ca 2+, Co 2+ and Ni 2+ herein). Due to the strong coordination ability, PA molecules may be self-assembled on the iron surface, forming a layer of organic thin film (here defined as PA film), without the help of additive metal ions. However, the comparison between PA film and PA–M coatings shows that PA–M coatings were much thicker (over 15 μm) and denser and also possessed much stronger anti-corrosion performance compared to the PA film. The present study provides a new path for the fabrication of environmentally-friendly PA-based chemical conversion coatings and further broadens the application range of PA in metal surface pretreatment.